Follicular Biochemical Characterization and Fatty Acid Metabolic Signatures of Follicles During Ovulation Process Reveal the Potential Mechanism for Ovarian Cyst Formation in Sows - Jingyuan Liang; Yanfei Deng; Song Fu; Juanru Cheng; Ruimen Zhang; Deshun Shi; Yu Pan; Sufang Yang (Metabolites)
Background/Objectives: As a well-known source of energy from feed, the significance of fatty acids in regulating the reproductive potential of livestock has received attention in recent years, especially follicular development. Moreover, successful ovulation is a process that is crucial for reproduction and fertility in domestic animals. Therefore, it is important to reveal the signatures of fatty acids in follicular fluid during mammalian ovulation, and this provides a possible method to prevent the occurrence of ovarian cysts in domestic animals. Methods: Pre-ovulatory follicles (n = 6) and peri-ovulatory follicles (n = 6) during normal ovulation, as well as cystic follicles (n = 6) in ovulation-deficient ovarian cyst were isolated and characterized, while follicular fluid was collected for targeted fatty acid metabolomics detection and analysis. Results: We have illustrated the anatomical and biochemical characterization of pre-ovulatory, peri-ovulatory, and cystic follicles. Subsequently, we identified changes in 51 fatty acids profiles in the follicular fluid. The highest proportion of fatty acids in the follicular fluid at three different ovulation stages is polyunsaturated fatty acids, among which the abnormality of the linoleic acid metabolism pathway was involved in ovulation defects in cystic follicles. Remarkably, we found that linoleic acid was significantly increased while arachidonic acid was significantly decreased in cystic follicles. Conclusions: Polyunsaturated fatty acids play a significant role in the follicular ovulation stage of sows. Among them, linoleic acid and arachidonic acid are closely related to the ovulation defects of cystic follicles, which suggests that identifying changes in important metabolic signatures may give us a better understanding of the pathogenesis of ovarian cyst.